2022
DOI: 10.1136/emermed-2021-212242.2
|View full text |Cite
|
Sign up to set email alerts
|

BET 1: Ruling out cerebellar infarct in the emergency department with CT scan

Abstract: A short-cut review of the available medical literature was carried out to establish whether CT scanning can rule out cerebellar infarction. After abstract review, two papers were found to answer this clinical question using the detailed search strategy. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these papers are tabulated. It is concluded that there is insufficient evidence to draw a conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Sometimes, strict application of ‘evidence-based’ medicine can yield conclusions that are either wrong, clinically misleading and/or harmful. Regarding the conclusion of the recent short-cut review about the accuracy of non-contrast brain CT in diagnosing cerebellar infarction,1 I strongly disagree that there is insufficient evidence that CT can or cannot exclude the condition in ED patients with ‘concerning features’ of vertigo.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Sometimes, strict application of ‘evidence-based’ medicine can yield conclusions that are either wrong, clinically misleading and/or harmful. Regarding the conclusion of the recent short-cut review about the accuracy of non-contrast brain CT in diagnosing cerebellar infarction,1 I strongly disagree that there is insufficient evidence that CT can or cannot exclude the condition in ED patients with ‘concerning features’ of vertigo.…”
mentioning
confidence: 98%
“…This could artificially inflate the sensitivity of CT. Furthermore, the short-cut review finding—that CT identified 42%–55% of cerebellar strokes—shows that CT cannot rule out cerebellar stroke with anywhere near the degree of accuracy needed in this situation 1…”
mentioning
confidence: 99%